NK cells are activated and primed for skin-homing during acute dengue virus infection in humans - Zimmer, Christine L.; Cornillet, Martin; Solà-Riera, Carles; Cheung, Ka-Wai; Ivarsson, Martin A.; Lim, Mei Qiu; Marquardt, Nicole; Leo, Yee-Sin; Lye, David Chien; Klingström, Jonas; MacAry, Paul A.; Ljunggren, Hans-Gustaf; et al. (Nature communications, 2019)
Despite animal models showing that natural killer (NK) cells are important players in the early defense against many viral infections, the NK cell response is poorly understood in humans. Here we analyze the phenotype, temporal dynamics, regulation and trafficking of NK cells in a patient cohort with acute dengue virus infection. NK cells are robustly activated and proliferate during the first week after symptom debut. Increased IL-18 levels in plasma and in induced skin blisters of DENV-infected patients, as well as concomitant signaling downstream of the IL-18R, suggests an IL-18-dependent mechanism in driving the proliferative NK cell response. Responding NK cells have a less mature phenotype and a distinct chemokine-receptor imprint indicative of skin-homing. A corresponding NK cell subset can be localized to skin early during acute infection. These data provide evidence of an IL-18-driven NK cell proliferation and priming for skin-homing during an acute viral infection in humans. Here, Zimmer et al. analyze the natural killer (NK) cell response in a patient cohort with acute dengue virus infection showing early NK cell activation and proliferation, and the data suggest that NK cell proliferation depends on IL-18 signaling, and that responding NK cells have a skin-homing phenotype.